Lines of Flight and Nomadic Trajectories: Visualising Rhizomatic Learning with Cartography - Kairiené, Aida; Mažeikienė, Natalija (Journal of Education Culture and Society, 2024)
Aim. This article presents the research on using cartography as a research method based on Gilles Deleuze and Félix Guattari’s (2004) insights. The aim of the study – to unfold and visualise students’ learning experiences in non-formal and informal learning contexts beyond the classroom. Methods. Cartography and rhizoanalysis. Cartography is a method of mapping (Wilmott, 2020). In order to create rhizomatic maps we used Deleuze and Guattari (2004) theoretical insights. The rhizoanalysis (Masny, 2015) was carried out according to Deleuze and Guattari’s (2004) rhizome principles: connectivity and heterogeneity multiplicity and rupture, cartography and decalcomania. The rhizoanalysis simultaneously reveals Alecia Youngblood Jackson and Lisa Mazzei’s (2012) process of "thinking with theory". Thirty-eight students from upper-grade classes participated in this research. Each student’s learning path was depicted as their rhizomatic journeys, using various concepts such as nomads, lines of flight, becoming. Results. The rhizoanalysis makes it possible to reveal students’ rhizomatic learning experiences, areas of interest and learning styles. Such a map challenges an existing hierarchical framework and conveys how students’ freely make connections through lines of flight and create their own learning paths. Conclusions. This study demonstrates cartography as a useful methodology for visualising students’ learning experiences. Also, this study is unique and distinctive because it reveals the nomadic trajectories of individual learners and offers a thorough investigation of their activity destinations. The researchers of this study advise that students’ non-formal and informal learning experiences be included into their formal education by using nomadic pedagogy.